CRISPR-Based Genome Editing for Nutrient Enrichment in Crops: A Promising Approach Toward Global Food Security - Kumar, Dileep; Yadav, Anurag; Ahmad, Rumana; Dwivedi, Upendra Nath; Yadav, Kusum (Frontiers in Genetics, 2022)
The global malnutrition burden imparts long-term developmental, economic, social, and medical consequences to individuals and their families, communities, and countries. Malnutrition results from global food system failure, which otherwise could have offered enough quantities of virtuous, nutritionally enriched and balanced meals, particularly to impoverished people. A promising and cost practical approach towards alleviating the problem of malnutrition is the biofortification of staple crops, especially grain and cereal crops, which is now acquired much attention in recent years and has induced a substantial shift in the direction of breeding programs. In recent years, the CRISPR-Cas genome editing tool has been extensively used in crop improvement because of its advantages: simpler design, low cost, high efficiency, good reproducibility, and quick cycle. Thus, CRISPR-Cas based genome editing has been utilized in the biofortification of a variety of crops such as rice, wheat, barley, maize including vegetable crops like potato and tomato for a variety of quality improvement traits such as aroma, starch, amylose, protein, GABA, olieic acid, shelflife, sweetness, anthocyanin, phytic acid, gluten, steroidal glycoalkaloids, disease and stress resistance, etc. The present review has critically discussed the biofortification of such crops through the CRISPR-Cas genome editing approach for nutraceutical enhancement in quality and quantity by targeting cytokinin metabolism